Resistência de tomateiro a geminivírus e a estresse hídrico - Oliveira, Alisson Marcel Souza de Oliveira (2016)
In tomato crop, one of the vegetables most grown in the world, pathogens and environmental stresses such as drought, are limiting factors and leads to yield reduction. This study aimed to evaluate tomato genotypes with different geminivirus resistance levels, and identify morphological and physiological characteristics associated with drought tolerance. In the first trial, 48 tomato genotypes, were infected with Tomato yellow vein streak virus (ToYVSV) using whiteflies as vectors (Bemisia argentifolii) and were evaluated using a rating scale ranging from 1 to 5, with 1 = no symptom (highly resistant plant) and 5 = severe symptoms (highly susceptible plant). Inbred lines bearing the gene Mi in association with the Ty-1 gene, both homozygous, showed a higher geminivirus resistance level than those genotypes bearing only one of these genes, and that hybrids bearing Mi and Ty-1 genes in heterozygosity. Genotypes with higher allelochemicals levels such as acylsugar and/or zingiberene also contributed to increase geminivirus resistance level conferred by Ty-1. In general, the presence of allelochemicals and/or the Mi gene in tomato genotypes reduces the symptoms of geminivirus due to the lower vector infestation. In the second trial, the treatments consisted of five genotypes of tomato: the TOM -684 and TOM-760 inbred lines, with low drought tolerance; the inbred lines BPX -441D-88-bulk and BPX-441D-55-bulk , previously characterized as resistant to blossom end rot induced by drought stress, and the hybrid F 1 (BPX-441D-88- bulk x TOM-760). The water supply restriction occurred 35 days after transplanting (DAT), it was provided only 20% of crop evapotranspiration (ETc). The genotypes BPX-441D-88-bulk, BPX -441D-55-bulk and the hybrid F 1 (BPX-441D-88-bulk x TOM-760), had the lowest aborted flowers and fruit with blossom end rot percentages. The hybrid F 1 (BPX-441D-88-bulk x TOM-760) showed higher chloroplastids pigments levels when compared to other genotypes, resistant and susceptible genotypes. The inbred lines BPX-441D-88-bulk and BPX-441D-55-bulk showed lower stomatal density in both abaxial and adaxial leaf surface, and in drought stress conditions, had higher gas exchange. The characteristics evaluated in this study are related to drought and can be used as a tool in tomato breeding programs.